Natural Disasters, Poverty and Inequality : New Metrics for Fairer Policies - Hallegatte, Stephane; Walsh, Brian (Taylor and Francis, 2021)
Conventional risk assessments underestimate the human and macroeconomic costs of disasters, leading to inefficient risk management strategies. This happens because conventional assessments focus on asset losses, neglecting important relationships between vulnerability and development. When affected by a hazard, poor households take longer to recover from disasters and are more likely to face long-term consequences. Forced to manage trade-offs between essential consumption and reconstruction, these households are more likely to face persistent health or education costs. This chapter proposes a review of existing research into the natural disaster-poverty-inequality nexus and the various metrics that can be used to measure disaster impacts, such as recovery times, economic (income or consumption) losses, poverty incidence, inequality, and welfare or well-being losses. Each of these metrics provides a different perspective on disaster costs and suggest different spatial and sectoral priorities for action. Focusing on the concepts of well-being losses and socioeconomic resilience, this chapter shows how more comprehensive accounting of disaster impacts can better inform disaster risk management and climate change adaptation strategies and support their integration into development and poverty-reduction policies.